Handbook of research on examining cultural policies through digital communication - Önay Dogan, Betül 1980-; Ünlü, Derya Gül 1991- (IGI Global, 2019)
"This book focuses on creating a cultural policy through digital communication and maintaining existing cultural policies digitally. It addresses aspects of cultural policy in digital communication such as digital communication in the process of understanding cultural values, digital in the production of contemporary cultures, digital integration of cultural data, language policy and digitalization from a cultural perspective"...